Morphological, Histological, and Histochemical Studies on the Adrenal Gland of the Japanese quail (Coturnix japonica) During the Post Hatching Period - Fadl , Saher; Abdel-maksoud, Fatma M.; Abou-Elmagd , Ahmed; Saleh , Abdelmohaimen M.M. (Journal of Advanced Veterinary Research, 2023)
The adrenal gland of the Japanese quail is a bilateral endocrine organ that is located in the abdominal cavity. The development of the adrenal gland begins in the pre hatching period and continues during the post hatching. The current study aimed to describe the anatomical and histological changes of the adrenal gland in Japanese quail during the post hatching period. The present study was carried on Japanese quail chicks, at ages of day of hatching, two- and four-weeks post-hatching. The dissected adrenal glands were investigated morphologically, histologically, and histochemically. In the current work, the interrenal tissue makes up most the adrenal parenchyma and the chromaffin mass gradually increase with the age. The interrenal tissue at the peripheral zone of the gland arranged into arch-like cords, becomes more prevalent throughout the gland with age, notably at five weeks. They were strongly positive for PAS especially on the day of hatching age but appeared negative by Grimelius argyrophilic stain. At the two weeks of age, chromaffin cells appeared in the form of triangular islets scattered between the interrenal cells. They are smaller and fewer than the interrenal cells, at the age of five weeks the chromaffin islets increased in size and concentrated at the central zone. Two types of chromaffin cells were observed by using Grimelius argyrophilic stain; one of them contain dark brown granules and the other is free from these granules. Finally, distinct morphological changes in the adrenal gland occur during the post-hatching phase.